Plan de negocios para el cultivo y exportación de brócoli en la ciudad de Atuntaqui - Iza Narváez, David Alejandro (2010)
Ecuador is the leading exporter of broccoli at the level of South America, growth in exports has reached 13% annually and imports about 22% recorded among the best business partners which include the United States, Germany, Japan and the Netherlands. The agricultural sector is the second main contribution in the GDP of Ecuador showing in 2009 to 9.8% for this year is forecast to generate a badge of 3.417 USD 540 thousand, broccoli production in 2009 was forecast at 92 720 metric tons which gives notice that there has been a growth of 22%. The market intelligence conducted found that the potential market is the United States and two additional alternatives: Germany and Holland is worth noting that these countries are producers of high demand broccoli but dissatisfaction on buyers and direct marketers. Customers of the company will be located through an extensive database that has the CORPEI and by associations of producers of broccoli who already show heavy demands upon the product. The Company has been structured so that it can cope with and effectively manage the issue / production-export business of broccoli, under the name "FRUTIVEG" Atuntaqui in the city of the province of Imbabura, which has one of the most favorable for growing broccoli for its climate and soil quality. It is worth mentioning that the name is the projection establishing strong expansion over the medium term, with its main campus in fruit and vegetables, "FRUTIVEG" represents the idea of expansion that longs to reach while meeting the demand for broccoli primarily as a pioneer of Company. Then we have proceeded to perform the rigorous study of the appropriate ways and appropriate for you can advertise the products you are online, INIAP, CORPEI, magazines and gigantography, establishing a marketing plan that stresses, advertises, impacts and sell the product by price, promotion and appropriate square. The project investment is 1.992 USD 448 with a recovery of capital in the third year, the IRR is 39% and NPV 007 1.502, which stimulates the feasibility of putting in place to generate adequate profits. If needed, there is the Contingency Plan which proposes appropriate actions to follow in case of casualties or dangerous risks for the Company.